AJT COGNITIVE TEST: RESPON HARAPAN BARU TERHADAP TES INTELIGENSI ANAK DI INDONESIA - Andi Halima; Eva Meizara Puspita Dewi; Eka Damayanti; Nurfajriyanti Rasyid (JURNAL SIPAKALEBBI, 2022)
Problems in the use of psychological tests are often found related to test items that are not culturally sensitive. Language adaptation in psychological tests is not enough to solve these cultural problems. The presence of the AJT Cognitive Test in Indonesia and its use in education is a new hope for the Intelligence test in Indonesia because it is developed according to local culture. Community service activities carried out by APPI Sulawesi in the form of training with the theme "Recognizing and Improving Children's Abilities with the AJT Cognitive Test" in September 2020 presented competent speakers and participated in this research 80 people who came from various regions in Indonesia and agencies and diverse professions. The way to measure the level of achievement of the success of this activity is in the form of providing a program evaluation using an instrument in the form of a questionnaire distributed via Google form. Evaluation questionnaire containing closed questions and open questions. Data is processed using descriptive statistical analysis. The findings show that the AJT Cognitive Test training is attractive to participants and the contents of the training material are to the needs of participants, and this training makes participants understand the components of the AJT Cognitive Test.